Combined multigene and morphological analysis reveals lineage-specific diversification of the neotropical freshwater crabs of the genus Fredius Pretzmann, 1967 (Brachyura, Pseudothelphusidae). Issue 1 (31st December 2022) - Mantelatto, F.L.; Souza-Carvalho, E.A.; Araujo, S.R.; Magalhães, C.
Abstract : The pseudothelphusid freshwater crabs of the genus Fredius Pretzmann, 1967 are distributed throughout northern South America and currently include 15 species. We investigated the phylogenetic relationship within the genus using mitochondrial (16S rRNA and COI) and nuclear (H3) genes for most of its representatives. Our set of molecular results (10 species) indicate that Fredius, as currently recovered, is formed by species included in three main lineages. In addition, the results revealed inconsistencies in the morphological identification of some species against the molecular positioning in the topology and suggested the presence of cryptic species, which must be morphologically reanalysed.